The Ross Shelf cavity water exchange variability during 1995-1998 - Bergamasco, A.; Ardizzon, G.; Carniel, S.; Meloni, R.; Sclavo, M. (Societa italiana di fisica, 2004)
This work aims at presenting an analysis of the evolution of the physical properties of a water column at the southern limit of the Ross Sea, Antarctica. Data has been collected over a four year period (from January 1995 to July 1998) by means of an oceanographic mooring (named mooring “F”) berthed a few miles north of theRoss IceShe lf at a depth of 600 m on thecon tinental shelf. The velocity and temperature measurements have been investigated seeking for ISW (Ice Shelf Water) outflow footprints. These outflows are irregular massive injections of cold water from below the Ice Shelf, flowing mainly across the cavity floor into the Ross Sea bottom layers. The study evidenced a large number of DISW outflow events (Deep Ice Shelf Water, the coldest and densest fraction of the ISW, the actual main object of the present study), characterized by an interannual variability that could turn out to bean important co-factor in thev ariations of theplane tary heat balance and climate instability. Differences in DISW outflow timings from biennium 1995-1996, during which a jet-like behaviour was dominating (each events was only a few days long), and 1997-1998 (with a few long and rather continous cold water outflows) have been detected. Moreover, in 1996 measurements evidenced a relatively long and warm period (about 110 days from March to July) characterized by thetotal absenceof DISW outflow, this interval being morethan twice longer with respect to any other similar ones registered during 1995, 1997 and 1998, and longer that any other warm period observed in the area during the early ’80s. The estimates of cold water exchanged during the four years return a more complicated framework: 1996 behaviour seems to be closer to the 1997 than to the 1995 one, with high fluxes and high volumes. 1995 can probably be considered as the ignition of an interannual anomaly, which climax is the long warm period of spring 1996.